2006
DOI: 10.1186/1477-7525-4-21
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of irritable bowel syndrome patients in different cultural settings

Abstract: BackgroundPersons with Irritable bowel syndrome (IBS) are seriously affected in their everyday life. The effect across different cultural settings of IBS on their quality of life has been little studied. The aim was to compare health-related quality of life (HRQOL) of individuals suffering from IBS in two different cultural settings; Crete, Greece and Linköping, Sweden.MethodsThis study is a sex and age-matched case-control study, with n = 30 Cretan IBS cases and n = 90 Swedish IBS cases and a Swedish control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
(25 reference statements)
2
31
0
2
Order By: Relevance
“…Sakata et al [27] reported that the factors affecting IBS differed greatly among individuals. Furthermore, in a study about quality of life (QOL) [28], it was shown that how people accept situations is different between races. For example, Swedish people considered disease more seriously than Greeks did, and it affected their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Sakata et al [27] reported that the factors affecting IBS differed greatly among individuals. Furthermore, in a study about quality of life (QOL) [28], it was shown that how people accept situations is different between races. For example, Swedish people considered disease more seriously than Greeks did, and it affected their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…However most clinical studies usually assessed symptomatic improvement or used only a summary score even if QOL was assessed. The pattern of bowel symptoms related to IBS seems to be similar across the country,29 but quality of life perceived by IBS patients varied depending on different cultural environments and countries rather than racial differences 30,31…”
Section: Discussionmentioning
confidence: 99%
“…Physical HRQoL refers to physical limitations in everyday functioning which are a result of bodily pain or low general health, while mental HRQoL reflects functional limitations resulting from negative mood, or poor mental and social functioning [41]. Compared to healthy controls, IBS patients have significantly lower quality of life scores [42], as do IBD patients [43]. When comparing the two patient groups, they show similarly reduced quality of life [43].…”
Section: Evaluation Of Hypothesismentioning
confidence: 96%